Crystal structure of poly[(μ 2-2,2′-[1,4-phenylenebis(methylenesulfanediyl)]dibenzoato-κ 4 O,O′:O″,O‴)-(μ 2-1,1′-([1,1′-biphenyl]-4,4′-diyl)bis(1H-benzimidazole)-κ 2 N:N′)cadmium(II)]dimethylformamide solvate, C51H41N5O5S2Cd - Li Bin; Chen Zhiwei; Wang Suna (Zeitschrift für Kristallographie - New Crystal Structures)
C51H41N5O5S2Cd, triclinic, P1‾ $P\overline{1}$ (no. 2), a = 10.8410(9) Å, b = 13.0458(11) Å, c = 17.4971(15) Å, α = 68.8880(10)°, β = 72.7460(10)°, γ = 85.661(2)°, V = 2203.3(3) Å3, Z = 2, R gt(F) = 0.0655, wR ref(F 2) = 0.1765, T = 298(2) K.